FAKTOR–FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI (Studi Pada SKPD Kota Pekanbaru) - Sumarni, Lili; Tanjung, Amries Rusli; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the influence of the factors that affect the quality of financial reports and organizational commitment as moderating. Based on Government Regulation No. 71 In 2010, the quality of the financial statements of the Central Government and the Regions must meet the qualitative characteristics. Factors studied include the internal control systems, financial accounting system application areas, the quality of human resources and organizational commitment as moderating. The research was conducted at SKPD Pekanbaru city government. Data collected by questionnaire as many as 108 copies, distributed to respondents who are staff or employees of the regional work units (SKPD) in Pekanbaru City Government. Questionnaires were distributed to 108 respondents, only successfully reassembled with complete answers obtained 86 respondents. Data were analyzed using SPSS 21.00. The test results showed that the system of internal control and financial accounting system application areas significant positive effect on the quality of financial statements of Local Government, while the quality of human resources has no effect. Organizational commitment can not be used as moderating variables. Organizational commitment as independent variables significantly influence the quality of financial statements.Keywords: internal control system, the quality of human resources, organizational commitment, and the quality of financial reports.